CONSOLIDATION MECHANISM OF GROUND IMPROVED BY A COMBINED DJMPVD METHOD - D. W. Zhang; S. Y. Liu; Y. J. Du; G. Y. Du (Lowland Technology International, 2009)
Dry Jet Mixed (DJM) and Prefabricated Vertical Drains (PVDs) were used in combination to enhance the performance of soft ground improvement in Huai-yan highway in China. To investigate the consolidation mechanism of ground improved by a combined DJM-PVD method, coupled two-dimensional mechanical and hydraulic numerical modeling was conducted in this study to analyze the well-instrumented ground improved by a combined DJM-PVD method in Huai-yan highway in China. The results indicate that the consolidation of the ground improved by a combined DJM-PVD method is accelerated by the drainage of PVDs, the stress concentration on DJM columns and the excess pore water pressure gradient resulting from the stress transfer between the surrounding soil and columns. It is observed that the high drainage capacity of PVDs accelerates the dissipation of the excess pore water pressure. The accelerated dissipation is explained as that upon the embankment loading, the stress concentration on the column occurs due to its higher stiffness than that of the surrounding soil, and thereby results in the reduction of the excess pore water pressure in the soil. The differential settlement develops between the soil and the column induces the transfer of stress between surrounding soil and column, which results in pore water pressure gradient in the surrounding soil and accelerates the consolidation.